Evaluation of PDs - Norasage Pattanadech; Rainer Haller; Stefan Kornhuber; Michael Muhr (My University, 2023)
Partial discharge (PD) testing of high-voltage equipment is essential in order to ensure that the equipment will operate with high reliably and at high efficiency. PD testing can be divided into in-house PD testing and on-site PD testing. Evaluation of in-house PD test results can be categorized as either PD testing for product R&D or PD testing for product verification. There are two main types of PD quantity used in the analysis of PD test results – basic PD quantity and derived PD quantity. Moreover, there are three basic PD quantities (aka dimensional PD quantities) to be considered during analysis of insulation condition – discharge magnitude, PD inception voltage, and PD extinction voltage. Two types of PD patterns – phase-resolved PD and PD pattern with polarity count for problem analysis – are generally used in PD problem analysis.
Keywords: Polarity (international relations); High voltage insulation and dielectric phenomena